Effect of heat treatment on the corrosion behavior of AISI 4135 steel under natural seawater film at different temperatures - Xiuming, Y.; Yanliang, H.; Wenjuan, Q.; Yadav, A.; De Marco, Roland (Electrochemical Science Group, 2014)
High strength steel has a prosperous future in catering the needs of marine applications especially the tapping of deep sea resources. The use of high strength steel will reduce the weight of steel structures and reduce the environment burden for the production of materials. Thus it is necessary to study the problems concerning the safety of high strength steel applications in marine environment. In this paper the corrosion behavior of heat treated AISI 4135 steel was studied by means of electrochemical techniques at different temperatures when it is covered by natural seawater film. The results showed that the corrosion rate of the steel increases with the elevation of temperature but the heat treatment processes have no profound effect on the corrosion. The expected mitigation of corrosion by tempering of quenched specimens could not be concluded based on the data of this research.